2019
DOI: 10.1007/s12210-019-00777-w
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selected growth regulators and culture media on regeneration of Daphne mezereum L. ‘Alba’

Abstract: Key message Tissue cultures are the only effective way to proliferate this valuable species (Daphne mezereum). These researches may help in solving the problem of reproduction of other woody plants. Abstract Daphne mezereum L. commonly known as February daphne or mezereon is a decorative shrub from the family Thymelaeaceae. It is a valuable nursery plant due to its high ornamental values, but its propagation by traditional methods is ineffective, therefore, little profitable. Micropropagation may be a good alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
(27 reference statements)
4
13
0
Order By: Relevance
“…Therefore, the use of appropriate concentration of auxin are important to control the growth and development of plants in vitro. This is confirmed by the result of research on Daphne mezereum L. ‘Alba’ where they reported optimum rooting formation using lower concentration of auxin [ 49 ]. The present study suggested that IAA at the concentration of 0.5-mg L −1 is the optimum to induce root.…”
Section: Resultssupporting
confidence: 63%
“…Therefore, the use of appropriate concentration of auxin are important to control the growth and development of plants in vitro. This is confirmed by the result of research on Daphne mezereum L. ‘Alba’ where they reported optimum rooting formation using lower concentration of auxin [ 49 ]. The present study suggested that IAA at the concentration of 0.5-mg L −1 is the optimum to induce root.…”
Section: Resultssupporting
confidence: 63%
“…Leaf samples from in vitro conditions (prior to transplanting) and 4-week-old acclimatized plants were collected for SEM examination. Following a fifteen-minute gradual dehydration with an increasing alcohol series (30,50,70,90, and 100%), the leaves were fixed in 2% (v/v) glutaraldehyde (Merck, Merck Specialities Pvt. Ltd., Mumbai, India) and left at room temperature for two hours.…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 99%
“…Cytokinins are adenine derivatives capable of inducing cell divisions in tissue cultures, initiating shoots and stimulating their proliferation and further growth, both of which are critical for in vitro multiplication efficiency. Exogenously applied cytokinins are more active in the presence of an auxin (Perveen et al 2011;Faisal et al 2018;Nowakowska et al 2019). Frequently used cytokinins are of natural origin such as zeatin (Zea), the 2-isopenthenyladenine (2iP), kinetin (Kin), and 6-benzyladenine (BA) or synthetic cytokinins such as thidiazuron (TDZ) (Pierik 1997).…”
Section: Introductionmentioning
confidence: 99%